Dimensões de variação em manuais aeronáuticos: um estudo baseado na análise multidimensional - Zuppardo, Maria Carolina (2014)
This study set out to identify the dimensions of variation that characterize aircraft manuals, apply the 1988 dimensions for English to aircraft manuals, and verify if there is statistically significant variation among aircraft manufacturers and models as well as types of manuals in terms of the dimensions of variation of aircraft manuals. The main theoretical underpinning for the research is provided by Corpus Linguistics, an area of Applied Linguistics based on the view of language as a probability system whose studies of language or language varieties involve the use of computational and interactive tools applied to large collections of texts held in electronic format (corpora). More specifically, the study presented here is informed by Multidimensional Analysis, a corpus-based approach for the study of associations between linguistic features and registers in large amounts of text through the use of statistical procedures in order to identify dimensions of variation. The corpus compiled for the study is comprised of operational and maintenance aircraft manuals of commercial and corporate aircraft, containing 10,009,040 words distributed across 154 texts. On the whole, the findings suggest that, in terms of placement of the corpus in the dimensions of variation for English defined by Biber in 1988, aircraft manuals are highly informational, non-narrative, with explicit references, abstract information, and covert persuasion. In addition, the multidimensional analysis revealed three dimensions of variation for aircraft manuals, namely: (1) Broad system descriptions; (2) Decision-making discourse versus Procedural discourse; e (3) Problem-solving discourse versus Specific parts descriptions. The study presented here may have made an original contribution to the English for Aviation areas in addition to the existing body of corpus-based research in that it determined the dimensions of variation of aircraft manuals and their salient linguistic features. The study also presents and discusses possible limitations and further research, as well suggestions for pedagogical applications of the findings